Modernism after the death of God : Christianity, fragmentation, and unification - Kern, Stephen (Routledge, an imprint of the Taylor & Francis Group, 2017)
"Modernism After the Death of God: Christianity, Fragmentation, and Unification explores the writing and philosophies of some of the most popular modernist figures studied today. This ground-breaking work, is an interpretation of the life and work of Friedrich Nietzsche, James Joyce, Sigmund Freud, D. H. Lawrence, Andre Gide, Martin Heidegger and Virginia Woolf that shows how each related to and drifted from religion in large part because they believed that Christian sexual morality had damaged or threatened to damage their love life" --